KEMELIMPAHAN PAKAN ALAMI PADA TANAH DASAR KOLAM INCEPTISOL YANG DIMAREL DENGAN ULTISOL - Saberina Hasibuan; Bambang Djadmo K; Kamiso Handoyo Nitimulyo; Eko Hanudin (UIR Press, 2014)
The quality of pond bottom soils is an important factor in fish cultures. The aims of this research were to find out the best composition natural feed to grow in Inceptisols pond bottom soil by marling it with Ultisols. There were 3 treatment combinations of I-U. The proportions are 70%:30%, 50%:50%, 30%:70% and a control (100%:0%). Each treatment was replicated 3 times. These mixtured soils were spread out at the bottom of 12 individual ponds (1 x 2 x 1 meter3), in 15 cm thickness. The soil physical, chemical and biological characteristic changes of the pond bottom were observed and analyzed. The study found that the physical fertility improvement through of marling Inceptisols pond bottom resulted in change of soil textures from sandy loam to clay loam and from sandy loam to clay. The chemical characteristic results showed that the ranges of ratio C/N was 4.31-6.81, Fe available was 6.39-17.76 ppm, K available was 60.14-68.25 ppm and CEC was 15.96-27.87 cmol(+)kg-1, respectively. The best treatment combinations was I-U that produced 46% clay content, which result in the highest abundanceof benthic algae and plankton production.